Recovery of copper, cobalt and phosphorous from semiconductor wastewater through fluidized-bed homogeneous granulation on the crystallization of metal phosphates - Bayon, Lester Lee E.
Green and sustainable strategies aim for the development of manufacturing processes that maximize the use of resources, instigating the semiconductor industry to adopt zero-liquid discharge policies. Complexity and variations in semiconductor wastewater effluents open an opportunity for resource recovery. One such opportunity is the potential recovery of heavy metals in chemical-mechanical polishing wastewater, and inorganic ions from etching and acid cleaning. The present work demonstrates the capabilities of homogeneous crystallization in fluidized-bed reactor as treatment technology to process water effluents for industrial reuse while simultaneously recovering precious resources such as copper, cobalt and phosphate. Experimental results revealed that the optimum conditions were achieved at effluent pH of 6.0 - 6.5 and [PO4-³]/ [Cu²?] of 1.25 for copper phosphate granulation, and at effluent pH of 7.75 - 8.0 and [PO4-³]/[Co²?] of 2.0 while for cobalt phosphate. Additionally, uniform crystal growth was attained due to appropriate fluidization and proper collision of the particles at upflow velocity 28.65 m h-1 with 0.51 kg Cu²? m-²h¯¹, and 40.11 kg Co²? m-²h¯¹ for copper and cobalt, respectively. The maximum copper and cobalt granulation were 96.07% and 98.8% respectively, whereas ~99% removal of both metal ions were attained at optimal parameters. Addition of EDTA and citrate inhibits crystal growth, decreasing the metal granulation capability by ~35% and ~24% from the optimal. Mixing a copper and cobalt ions in fluidized-bed homogenous crystallization process was also investigated in which the highest granulation of 95.9% was attained at effluent pH of 6.50 for copper, and 96.8% at effluent pH of 7.50 for cobalt with an equimolar metal concentration of 7.0mM and phosphate-metal molar ratio of 1.60. The granules were analyzed using XRD and SEM-EDS. The recovered crystals were identified as mineral libethenite (Cu2(PO4)OH) and cobalt phosphate hydrate (Co3(PO4)2-8H2O) as main recovere